THE INFLUENCE OF ACADEMIC SUPERVISION ON IMPROVING ELEMENTARY SCHOOL TEACHERS’ COMPETENCE - Handriadi Handriadi; Ali Yusron; Deka Meuthia Novari; Khoirul Amani; Muh. Aksa (International Journal of Educatio Elementaria and Psychologia, 2025)
Teacher competence plays a crucial role in determining the quality of education in elementary schools. However, many teachers face challenges in effectively implementing pedagogical strategies, classroom management, and curriculum delivery, which can impact student outcomes. Academic supervision has emerged as a vital mechanism for supporting and enhancing teacher performance by providing constructive feedback, mentoring, and professional development opportunities. This study aims to investigate the influence of academic supervision on improving elementary school teachers’ competence. A mixed-methods research design was employed, incorporating quantitative and qualitative approaches. The study involved 50 elementary school teachers, with data collected through teacher competence assessments, supervision activity records, and in-depth interviews. The findings revealed that academic supervision significantly improved teachers’ pedagogical and professional competencies. These results underscore the value of academic supervision as a strategic tool for enhancing teacher effectiveness and, consequently, educational quality. The study concludes by recommending the systematic implementation of academic supervision programs in elementary schools to optimize teacher performance and professional growth.